2016
DOI: 10.1111/jog.12988
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐delivery fibrinogen predicts adverse maternal or neonatal outcomes in patients with placental abruption

Abstract: Aim: Placental abruption is a severe obstetric complication of pregnancy that can cause disseminated intravascular coagulation and progress to massive post-partum hemorrhage. Coagulation disorder due to extreme consumption of fibrinogen is considered the main pathogenesis of disseminated intravascular coagulation in patients with placental abruption. The present study sought to determine if the pre-delivery fibrinogen level could predict adverse maternal or neonatal outcomes in patients with placental abruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
(35 reference statements)
2
23
1
1
Order By: Relevance
“…The present study suggests that the use of fibrinogen concentrate would be particularly effective for massive obstetric haemorrhage, although recent data relating to non-obstetric haemorrhage show no benefits for fibrinogen concentrate administration19. This may be because pregnancy enhances coagulation and reduces fibrinolysis2021, which affects consumption of fibrinogen and hyperfibrinolysis in cases of massive obstetrical haemorrhage. In addition, the use of fibrinogen concentrate and FFP is the usual treatment method in many countries.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The present study suggests that the use of fibrinogen concentrate would be particularly effective for massive obstetric haemorrhage, although recent data relating to non-obstetric haemorrhage show no benefits for fibrinogen concentrate administration19. This may be because pregnancy enhances coagulation and reduces fibrinolysis2021, which affects consumption of fibrinogen and hyperfibrinolysis in cases of massive obstetrical haemorrhage. In addition, the use of fibrinogen concentrate and FFP is the usual treatment method in many countries.…”
Section: Discussioncontrasting
confidence: 52%
“…Consequently, rapid fibrinogen supplementation immediately improves coagulopathy and achieves haemostasis. Therefore, as shown in Table 4, the use of fibrinogen concentrate would be very beneficial in the early stages of consumption coagulopathy caused by placental abruption because it would minimise blood loss and transfusion volume2127.…”
Section: Discussionmentioning
confidence: 99%
“…In COH, coagulopathy easily develops due to the physiological change of blood coagulation and fibrinolytic function in pregnant women during late pregnancy, and it is difficult to evaluate the severity due to the volume of blood loss . Blood fibrinogen concentration has been suggested as an indicator of its severity …”
Section: Introductionmentioning
confidence: 99%
“…We believe this was because the ruptured dilated veins due to the myometrial sectioning were exposed to amniotic fluid, resulting in a DIC type of amniotic fluid embolism, although there were no severe cardiopulmonary symptoms involved in this case. Previous studies indicated that fibrinogen levels <87 mg/dL were associated with a very high rate (95.2%) of DIC requiring massive transfusions . Therefore, the extremely low fibrinogen levels found in similar cases might be a key signal indicating the need for prompt transfusion and surgical treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies indicated that fibrinogen levels <87 mg/dL were associated with a very high rate (95.2%) of DIC requiring massive transfusions. 7 Therefore, the extremely low fibrinogen levels found in similar cases might be a key signal indicating the need for prompt transfusion and surgical treatment. Uterine artery embolization might be an option for treating obstetric hemorrhage.…”
Section: How Should It Be Treated?mentioning
confidence: 99%